Hocus Pocus [videorecording (Blu-Ray)] - Kirschner, David, 1955-; Garris, Mick; Cuthbert, Neil; Midler, Bette; Parker, Sarah Jessica; Najimy, Kathy; Katz, Omri, 1976-; Birch, Thora; Shaw, Vinessa, 1976-; Debney, John; Narita, Hiro, 1941- (Disney, 2018)
After 300 years, three sister witches are resurrected in Salem Massachusetts on Halloween night, and it us up to two teenagers, a young girl, and an immortal cat to put an end to the witches' reign of terror once and for all.